A model for the interaction of dislocations with planar defects based on Allen–Cahn type microstructure evolution coupled to strain gradient elasticity. (May 2021) - Budnitzki, M.; Sandfeld, S.
Abstract: In classical elasticity theory the stress-field of a dislocation is characterized by a 1 ∕ r -type singularity. When such a dislocation is considered together with an Allen–Cahn-type phase-field description for microstructure evolution this leads to singular driving forces for the order parameter, resulting in non-physical (and discretization-dependent) predictions for the interaction between dislocations and phase-, twin- or grain-boundaries. We introduce a framework based on first strain gradient elasticity to regularize the dislocation core. It is shown that the use of strain energy density that is quadratic in the gradient of elastic deformation results in non-singular stresses but may result in singular driving forces, whereas a strain energy, which is quadratic in the gradient of the full deformation tensor, regularizes both stresses and driving forces for the order parameter and is therefore a suitable choice. The applicability of the framework is demonstrated using a comprehensive example.